Desenvolvimento de equipamento sanitizante com tecnologia UVC e ozônio para auxílio aos esforços de combate à pandemia de COVID-19 - Remuszka, Bruno (2021)
This research aims to develop a sanitization system based on the use of ozone gas and ultraviolet radiation. Apply these agents in a controlled volume to reduce the microbial load of the same volume, thereby inhibiting the pathogen within the fomites. This development was motivated by the Covid-19 pandemic, as cited by several works. Viruses are susceptible to UVC radiation just as ozone also affects microbial structures. Based on these studies and the health and economic crisis, we developed equipment to fight the spread of the pandemic that was ravaging the world. According to the state of New York (USA) which presented 60% of the admissions of covid-19 were of people who were fulfilling social isolation and some other studies reported that the SARS-CoV2 virus was capable of being keep active on surfaces for a long period, motivated us to develop the equipment with the purpose of sanitizing objects to reduce contagion. According to the first in vitro analysis we achieved a significant reduction in microbial life which, according to the Brazilian standard ABNT NBR ISO 14937, is the expected result for sterilizing agents. This positive result motivated us to evolve the product into a sterilizing agent in accordance with current sanitary standards.